Palaeoecology of giraffe tracks in Late Pleistocene aeolianites on the Cape south coast - Charles Helm; Hayley Cawthra; Richard Cowling; Jan De Vynck; Curtis Marean; Richard McCrea; Renee Rust (South African Journal of Science, 2018)
Until now there have been no reliable historical or skeletal fossil records for the giraffe (Giraffa camelopardalis) south of the Orange River or northern Namaqualand. The recent discovery of fossil giraffe tracks in coastal aeolianites east of Still Bay, South Africa, significantly increases the geographical range for this species, and has implications for Late Pleistocene climate and vegetation in the southern Cape. Giraffe populations have specialised needs, and require a savanna ecosystem. Marine geophysical and geological evidence suggests that the broad, currently submerged floodplains of the Gouritz and Breede Rivers likely supported a productive savanna of Vachellia karroo during Pleistocene glacial conditions, which would have provided a suitable habitat for this species. We show evidence for the hypothesis that the opening of the submerged shelf during glacial periods acted as a pathway for mammals to migrate along the southern coastal plain.